Association between symptoms of sleep apnea and problem behaviors in young adult twins and siblings. Issue 7 (6th May 2021) - Madrid-Valero, Juan J.; Barclay, Nicola L.; Rowe, Richard; Perach, Rotem; Buysse, Daniel J.; Ordoñana, Juan R.; Eley, Thalia C.; Gregory, Alice M.
Abstract: Background: Sleep apnea is one of the most common sleep disorders and it is related to multiple negative health consequences. Previous studies have shown that sleep apnea is influenced by genetic factors. However, studies have not investigated the genetic and environmental influences of symptoms of sleep apnea in young adults. Furthermore, the underpinnings of the relationship between apnea symptoms and internalizing/externalizing problems are unknown. The objectives of this study were to estimate the magnitude of: (1) genetic and environmental influences on self-reported apnea symptoms; (2) the relationship between self-reported apnea symptoms and internalizing/externalizing traits; (3) genetic and environmental influences on the associations between self-reported apnea symptoms, internalizing behaviors and externalizing behaviors. Methods: In a twin/sibling study, univariate and multivariate models were fitted to estimate both individual variance and sources of covariance between symptoms of sleep apnea and internalizing/externalizing behaviors. Results: Our results show that genetic influences account for 40% of the variance in sleep apnea symptoms. Moreover, there are modest associations between depression, anxiety and externalizing behaviors with apnea symptoms (ranging from r = 0.22–0.29). However, the origins of these associations differ. For example, whereas most of the covariation between symptoms of depression and sleep apnea can be explained by genes (95%), there was a larger role for the environment (53%) in the association between symptoms of anxiety and sleep apnea. Conclusions: Genetic factors explain a significant proportion of variance in symptoms of apnea and most of the covariance with depression.